Impact Of Information Technology In The Field Of Physical Activity And Physical Culture - Ikromjon Yuldashov (Euro Asian Journal Publishing, 2024)
It is known that the field that forms the social essence of a person in accordance with the needs of society is called the system of public education, and the person who implements it is called a teacher. From time immemorial, attention has been paid to the personal social qualities of teachers, and the requirements for teachers have become more sophisticated and complex, based on the requirements of each era
Keywords: physical education; physical training; sports